The Healer's Foundation: A Model of Self-Awareness, Self-Efficacy, and Social Support in Fostering Counselor Students' Self-Care - Setiyowati, Arbin Janu; Jaafar, Wan Marzuki Wan; Rachmawati, Indriyana; Atmoko, Adi; Indreswari, Henny; Probowati, Devy (Islamic Guidance and Counseling Journal, 2025)
Counselor Students, while seen as key providers of counseling and guidance services in educational settings, frequently face challenges stemming from insufficient self-care practices. The absence of these practices often leads to psychological difficulties that compromise their ability to fully embody the characteristics of effective counselors. This situation raises concerns about counselor students’ readiness to assume professional responsibilities and maintain long-term effectiveness in their roles. Therefore, the objective of this study is to investigate the impact of self-awareness, self-efficacy, and social support on the self-care of prospective counselor students, and to develop a comprehensive theoretical framework tailored specifically to their needs. This study employed an Ex Post Facto Causal Relationship Explanatory design. A sample of 277 students (38 males and 239 females) was selected using convenience sampling. Data were collected using four validated and reliable instruments—the Self-Efficacy Scale, the Self-Awareness Scale, Sarafino's Social Support Scale, and the Mindful Self-Care Scale. Data were analyzed through Structural Equation Modeling (SEM) to examine the relationships between the variables. The obtained results showed that significant relationships existed between self-awareness, self-efficacy, and social support with self-care. This research underscored the significance of harmonizing the pre-service Guidance and Counseling education curriculum with the sole purpose of cultivating self-care practices among students through synchronized learning.